Home-ownership and Economic Performance of Immigrants in Germany - Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
This paper analyzes the home-ownership gap between native and immigrant households in Germany, paying particular attention to the assimilation process of immigrant households.A double cohort approach is applied to investigate the effect of the duration of residence in Germany on the homeownership probability of immigrant households.Moreover, focusing on homeowners, differences in the housing quality between native and immigrant households are being examined.The estimates indicate that immigrant households are less likely to own their primary residence than comparable native households. Since the effect of the duration of residence in Germany on the home-ownership probability turns out to be insignificant, the empirical findings suggest that an assimilation process in home-ownership between native and immigrant households does not take place. Finally, differences in housing quality measures become insignificant after controlling for socioeconomic characteristics and contextual factors of native and immigrant households in an interacted model.
Keywords: F22; R21; I31; 330; Home-ownership; International Migration; Assimilation